1997
DOI: 10.1177/096120339700600311
|View full text |Cite
|
Sign up to set email alerts
|

Systemic lupus erythematosus with acanthosis nigricans, hyperpigmentation, and insulin receptor antibody

Abstract: Acanthosis nigricans, insulin receptor antibody, and systemic lupus erythematosus are associated in the potentially lethal syndrome of type B insulin resistance. Hyperpigmentation has been reported rarely, while glucose intolerance is common in these patients. We report an adolescent girl with acanthosis nigricans, hyperpigmentation, insulin receptor antibody, and systemic lupus erythematosus without glucose intolerance. Insulin resistance may be mild or transient in some patients with type B insulin resistanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…45 These patients tend to have other autoimmune diseases, most often systemic lupus erythematosus, but also Sj枚gren's syndrome, progressive systemic sclerosis, Hashimoto's thyroiditis, and autoimmune thrombocytopenia. 30,39,46 The Berardinelli-Seip (congenital) and Lawrence (acquired) syndromes of generalized lipodystrophy involve complete absence of subcutaneous fat and may be associated with AN, owing to extreme insulin resistance and hyperandrogenism. 4,47,48 AN may also be a component of numerous other conditions including Hirschowitz's syndrome, 49 polycystic ovarian syndrome, 7 Donohue's syndrome (leprechaunism), 50 Rabson-Mendenhall syndrome, 51 Alstr枚m syndrome, 52 familial partial lipodystrophy (Dunnigan type), Crouzon's syndrome, Bloom syndrome, and PraderWilli syndrome.…”
Section: Syndromic Anmentioning
confidence: 99%
“…45 These patients tend to have other autoimmune diseases, most often systemic lupus erythematosus, but also Sj枚gren's syndrome, progressive systemic sclerosis, Hashimoto's thyroiditis, and autoimmune thrombocytopenia. 30,39,46 The Berardinelli-Seip (congenital) and Lawrence (acquired) syndromes of generalized lipodystrophy involve complete absence of subcutaneous fat and may be associated with AN, owing to extreme insulin resistance and hyperandrogenism. 4,47,48 AN may also be a component of numerous other conditions including Hirschowitz's syndrome, 49 polycystic ovarian syndrome, 7 Donohue's syndrome (leprechaunism), 50 Rabson-Mendenhall syndrome, 51 Alstr枚m syndrome, 52 familial partial lipodystrophy (Dunnigan type), Crouzon's syndrome, Bloom syndrome, and PraderWilli syndrome.…”
Section: Syndromic Anmentioning
confidence: 99%
“…The association of AN with autoimmune disorders like SLE and autoimmune thyroiditis complicated with type B insulin resistance have been reported. [ 6 7 ] A case of generalized AN involving an area from the mucosa of the larynx to the esophagogastric junction, accompanied by autoimmune manifestations but not type B insulin resistance, was described by Kondo et al [ 8 ] The association of scleroderma with AN was described way back in 1966 by Cope et al The patient had profuse blackish villous overgrowth over axillae and inframammary regions along with diffuse systemic sclerosis. [ 9 ] Such association has also been described by Duperrat et al [ 10 ] in 1955 and by Sugawara et al [ 11 ] in 1980.…”
Section: Discussionmentioning
confidence: 99%
“…IRA has been described in several diseases including diabetes with acanthosis nigricans, Hashimotos' thyroiditis, primary biliary irrhosis, progressive systemic sclerosis, Sjogren's syndrome and SLE. [4][5][6][7][8][9] It was reported that SLE is the most common autoimmune disease complicated with IRA. Rosenstein, et al 12 have tested sera from 26 patients with SLE for the presence of IRA, and they found 3.8% of the patients were positive for IRA.…”
Section: Discussionmentioning
confidence: 99%
“…SLE with AIH is rare. Review of the literature showed only eight such cases [2][3][4][5][6][7][8][9] (Table 1), of which one case was related to IAA, seven cases were associated with IRA and there was no case simultaneously complicated with IAA and IRA. We first reported one Chinese patient with SLE presenting as recurrent hypoglycaemia with both IAA and IRA.…”
Section: Introductionmentioning
confidence: 99%